Motion Graphics Video as an Effective Promotional Media through Design Method: A Case Study of FitAcademy Application Design - Juanda, Edwar; Pratiwi, Wilsa; Khaqi, Rizal Bay (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2026)
The rapid development of technology today plays an important role in life, especially in the field of education. The FitAcademy Application is one of the developing digital platforms that requires promotion and visual improvement. Based on the results of the analysis carried out by the previous author, motion graphics are a promotional tool that has the potential to convey promotional messages and can bridge the density of information and audience attention. This design uses the design thinking method which goes through 5 stages of empathize, define, ideate, prototype, and test for a deeper understanding of the target audience of the design. Through Jobs to Be Done, a solution statement was obtained that this design will display the advantages of the FitAcademy Application, as well as build the perception that the FitAcademy application is here to support user needs activities. The results of the trial work show that the design created is able to meet user expectations in finding a learning application that suits their needs, both in terms of visual elements and the promotional messages conveyed.